Experience of the use of cerebral embolic protection device during transcatheter aortic valve replacement - ZHANG, Lan; LIU, Xinmin; XI, Ziwei; YUAN, Fei; YAO, Jing; JIANG, Zhengming; YAN, Yunfeng; SONG, Guangyuan (Zhejiang da xue xue bao. Journal of Zhejiang University. Medical sciences. Yi xue ban, 2025)
To evaluate the feasibility, efficacy and safety of Sentinel cerebral embolic protection device (CEPD) during transcatheter aortic valve replacement (TAVR). This study is a subgroup analysis of the China Moderate to Severe Valvular Heart Disease Registry, which has been registered at the Chinese Clinical Trial Registry (ChiCTR2300075006). Patients undergoing TAVR with the Sentinel CEPD from October 2023 to September 2024 were retrospectively enrolled. A total of 80 patients were included, with a median age of 72 (68, 76) years, including 52 males (65.0%) and 28 females (35.0%); 62 patients (77.5%) with tricuspid valves, and 18 patients (22.5%) with bicuspid valves; 34 patients (42.5%) with type Ⅰ aortic arch, 24 patients (30.0%) with type Ⅱ aortic arch, 12 patients (15.0%) with type Ⅲ aortic arch, and 10 patients (12.5%) with bovine-type aortic arch. Clinical data of the patients were summarized and analyzed. The primary endpoints were success rate of Sentinel CEPD implantation, as well as all-cause death, symptomatic stroke, transient ischemic attack, and Sentinel CEPD access vessel complications during hospitalization and within 30 days postoperatively. In the 80 patients, self-expanding valves were used in 68 cases (85.0%) and balloon-expandable valves in 12 cases (15.0%). Seventy-nine patients (98.8%) successfully underwent TAVR with Sentinel CEPD deployment. Macroscopically visible debris was captured in 92.5% (74/80) by filters of Sentinel CEPD. Although the procedure time for Sentinel CEPD placement was slightly longer in patients with bovine-type aortic arch, there was no statistically significant difference in deployment time among different aortic arch types ( >0.05). During hospitalization and within 30 days postoperatively, only one case of transient ischemic attack occurred, and there was no all-cause mortality, symptomatic stroke, or access-site vascular complications related to the Sentinel CEPD observed. The Sentinel CEPD demonstrates high feasibility across aortic arch types, potential efficacy in embolic capture, and excellent safety in TAVR.